Malta : 2009 Article IV Consultation; Staff Report; Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Malta. (IMF Staff Country Reports; Country Report ;, 2009)
Malta's financial sector has so far weathered the global turmoil relatively unscathed; the real economy has been decelerating since the last quarter of 2008. The staff report for Malta's 2009 Article IV Consultation underlies economic developments and policies. The fiscal position deteriorated sharply in 2008, owing to one-offs and spending slippages. The current account deficit improved to 5 1\2 percent of GDP. The immediate goal for fiscal policy should be to mitigate the negative spillovers on activity from the global crisis without compromising the already fragile public finances.